The association between living habits, physical activity level and sarcopenia in chinese older adults with type 2 diabetes mellitus: a cross-sectional study - Yue, Yiting; Shen, Huaping; Li, Hongmei; Zhang, Yongjing; Zhao, Yiwei; Zhang, Rui; Xue, Xiaoyan (Frontiers in Public Health, 2025)
ObjectiveSarcopenia significantly impacts quality of life and increases morbidity in older adults with type 2 diabetes mellitus (T2DM). This study aimed to investigate the association between Living habits, physical activity levels, and sarcopenia in this population.MethodsA cross-sectional study included 65 older adults with T2DM from a tertiary hospital in Shanxi Province, China. Dietary habits were assessed using a 3-day dietary recall method. Physical activity levels were quantified using the International Physical Activity Questionnaire (IPAQ) and categorized (high/moderate/low) based on metabolic equivalent (MET)-minutes/week. Sleep patterns were evaluated using the Pittsburgh Sleep Quality Index (PSQI), with regular sleep defined as 7–9 h nightly and a PSQI score ≤ 5. Sarcopenia was diagnosed according to the 2019 Asian Working Group for Sarcopenia (AWGS) criteria. Participants were categorized into sarcopenia and non-sarcopenia groups. Clinical data were compared, and multivariate logistic regression analyzed associations between lifestyle factors, physical activity, and sarcopenia.ResultsThe proportions of regular exercise, regular sleep, balanced diet, and high physical activity were significantly lower in the sarcopenia group (P < 0.05). Multivariate analysis identified regular exercise (OR = 0.42, 95% CI: 0.25–0.71), regular sleep (OR = 0.56, 95% CI: 0.33–0.94), balanced diet (OR = 0.61, 95% CI: 0.37–0.99), and high physical activity (OR = 0.48, 95% CI: 0.29–0.80) as protective factors against sarcopenia (all P < 0.05).ConclusionLiving habits and physical activity levels are significantly associated with sarcopenia risk in older adults with T2DM, suggesting potential targets for prevention strategies.